The Leadership Gender Gap in HEI Spaces - A Conceptual Framework - Singh, Archana; Parandhaman, B.; Saini, Dimple (Prabandhan: Indian Journal of Management, 2021)
Purpose : The purpose of the paper was to recognize and categorize the key enablers of leadership gender gap in HEI (higher education institutions) spaces and to model these for the education sector. The research paper was an attempt to develop a conceptual framework addressing the leadership gender gap in HEI spaces. We used extant literature review and expert opinions to recognize the enablers and barriers to leadership gender gap in HEI spaces for women. Research Design : The research process was systematically framed. It comprised of primary and secondary data. We used TISM (total interpretive structural modelling) as a tool to understand linkages between latent variables and to individually deduce and diagnose the transitive relation between the variables. The proposed model is further extended to understand the nature of the variables calibrated using fuzzy MICMAC analysis. Findings : The hierarchical relationship between the variables shows how leadership style, gender audit, and feminization in HEIs is mediated through gender leadership and women's status leading to gender inclusion based on which the TISM Model of Leadership Gender Gap in HEI Spaces has been obtained as the outcome. Research Limitations : The study was based on expert opinion and can be statistically tested by using any advanced techniques in order to fully utilize the advantage of this methodology. The framework explains the complicated associations among the enablers, which can be further validated with a larger sample size statistically. Originality/Value : This paper made an attempt to contribute to the field of HEI spaces, which is the need of the time. This is an original and novel study conducted to understand about the leadership gender gap in Indian HEIs by utilizing the TISM approach.